Difficult airway management in a patient with upper airway obstruction due to alkali ingestion: A case report. (October 2022) - Taguchi, Azusa; Fukaguchi, Kiyomitsu; Fukui, Hiroyuki; Sekine, Ichiro; Yamagami, Hiroshi
Abstract: Background: Ingestion of alkaline substances can cause mucosal damage and upper airway obstruction, which is a serious and potentially fatal complication. Case presentation: An 80-year-old patient ingested a small amount of alkaline liquid and presented to our hospital with burning sensations in the throat. Within two hours of arrival, the edema in the epiglottis rapidly worsened with excessive secretion, resulting in upper airway obstruction. We attempted to intubate the patient using fiberoptic bronchoscopy followed by a successful intubation using a video laryngoscope. Conclusion: Alkali ingestion can cause upper airway obstruction with excessive secretion. A video laryngoscope may be successful alternative tool for tracheal intubation in such situation especially in case of failed intubation by fiberoptic bronchoscopy. Highlights: Alkali ingestion can cause upper airway obstruction with excessive secretion. Upper airway obstruction can be rapidly worsened within a few hours. Intubation with fiberoptic bronchoscopy is not recommended in such a situation.